Healthcare professionals' views on how palliative care should be delivered in Bhutan: A qualitative study. - Tara Devi Laabar; Christobel Saunders; Kirsten Auret; Claire E Johnson (Public Library of Science (PLoS), 2022)
Palliative care aims to relieve serious health-related suffering among patients and families affected by life-limiting illnesses. However, palliative care remains limited or non-existent in most low- and middle- income countries. Bhutan is a tiny kingdom in the Himalayas where palliative care is an emerging concept. This study aimed to explore the views of Bhutanese healthcare professionals on how palliative care should be delivered in Bhutan. It is a component of a bigger research program aimed at developing a contextual based palliative care model for Bhutan. This is a descriptive qualitative study. Eleven focus group discussions and two in-depth interviews were conducted among healthcare professionals, recruited through purposeful sampling, from community health centres, district hospitals, regional and national referral hospitals, and the traditional hospital in Bhutan. The participants in this study emphasized the need for suitable palliative care policies; education, training and awareness on palliative care; adequate access to essential palliative care medicines; adequate manpower and infrastructure; and a multi-disciplinary palliative care team. Participants confirmed a socially, culturally and spiritually appropriate approach is crucial for palliative care services in Bhutan. Despite palliative care being a young concept, the Bhutanese healthcare professionals have embraced its importance, emphasized its urgent need and highlighted their views on how it should be delivered in the country. This study will help inform the development of a public health-focused palliative care model, socially, culturally and spiritually applicable to the Bhutanese people, as recommended by the World Health Organization.